x 7 *log(x)
7^x*log(x)
Se aplica la regla de la derivada de una multiplicación:
ddxf(x)g(x)=f(x)ddxg(x)+g(x)ddxf(x)\frac{d}{d x} f{\left(x \right)} g{\left(x \right)} = f{\left(x \right)} \frac{d}{d x} g{\left(x \right)} + g{\left(x \right)} \frac{d}{d x} f{\left(x \right)}dxdf(x)g(x)=f(x)dxdg(x)+g(x)dxdf(x)
f(x)=7xf{\left(x \right)} = 7^{x}f(x)=7x; calculamos ddxf(x)\frac{d}{d x} f{\left(x \right)}dxdf(x):
ddx7x=7xlog(7)\frac{d}{d x} 7^{x} = 7^{x} \log{\left(7 \right)}dxd7x=7xlog(7)
g(x)=log(x)g{\left(x \right)} = \log{\left(x \right)}g(x)=log(x); calculamos ddxg(x)\frac{d}{d x} g{\left(x \right)}dxdg(x):
Derivado log(x)\log{\left(x \right)}log(x) es 1x\frac{1}{x}x1.
Como resultado de: 7xlog(7)log(x)+7xx7^{x} \log{\left(7 \right)} \log{\left(x \right)} + \frac{7^{x}}{x}7xlog(7)log(x)+x7x
Simplificamos:
7x(xlog(7)log(x)+1)x\frac{7^{x} \left(x \log{\left(7 \right)} \log{\left(x \right)} + 1\right)}{x}x7x(xlog(7)log(x)+1)
Respuesta:
x 7 x -- + 7 *log(7)*log(x) x
x / 1 2 2*log(7)\ 7 *|- -- + log (7)*log(x) + --------| | 2 x | \ x /
/ 2 \ x |2 3 3*log(7) 3*log (7)| 7 *|-- + log (7)*log(x) - -------- + ---------| | 3 2 x | \x x /